1999
DOI: 10.1021/ja983480r
|View full text |Cite
|
Sign up to set email alerts
|

Ground- and Excited-State Reactions of Norbornene and Isomers: A CASSCF Study and Comparison with Femtosecond Experiments

Abstract: The ground-state and 1 (ππ*)-state potential energy surfaces of norbornene and isomeric C 7 H 10 species were mapped using CASSCF theory and the 6-31G* basis set and compared with the results of femtosecond experiments on norbornene retro Diels-Alder reactions. Computations explored stepwise and concerted retro Diels-Alder pathways, [1,3]-sigmatropic shifts, and [1,2]-sigmatropic shifts originating from the 1 (ππ*)-state or ground-state surfaces. Extremely efficient decay occurs from the excited state to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
92
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 45 publications
14
92
0
Order By: Relevance
“…45 In addition, the AM1 method yields relatively small energy values for deformation from the symmetric structure, which is consistent with some ab initio and density functional theory calculations. 46,47 Thus, the dynamics of this reaction using the AM1 method should provide at least qualitative results consistent with higher level electronic structure methods. …”
mentioning
confidence: 80%
“…45 In addition, the AM1 method yields relatively small energy values for deformation from the symmetric structure, which is consistent with some ab initio and density functional theory calculations. 46,47 Thus, the dynamics of this reaction using the AM1 method should provide at least qualitative results consistent with higher level electronic structure methods. …”
mentioning
confidence: 80%
“…[36±43] Since the process of funneling through a CI is very efficient, the nonradiative decay from the upper surface to the lower one usually occurs within a single vibrational period. [42,43] Furthermore, the structural information of a CI may provide significant insight into the mechanism of product formation from a ™photochemically heated∫ ground-state species. [2, 43,44] Schematically, the bifurcated character (with respect to the gradient difference (x 1 ) and nonadiabatic coupling (x 2 ) vectors) of a CI can be represented by a single crossing point of a double cone formed by two intersecting surfaces along the (n À 2)-dimensional hyperline, where n is the number of the degrees of freedom in the molecule.…”
Section: Conical Intersections and Avoided Crossingsmentioning
confidence: 99%
“…After the finding of the importance of photoinduced ICT processes in biological systems such as photosynthesis, [5] interest in molecular donor-acceptor systems has increased significantly. [6][7][8][9][10][11][12][13][14] For several years, the dual-fluorescence properties of donor-acceptor systems have been used for studying molecular switches. [15][16][17][18][19] It was found that changes in molecular structure and conjugated system can induce very different optical and physical properties in D-p-A compounds.…”
Section: Introductionmentioning
confidence: 99%